2018
DOI: 10.1002/cptc.201800015
|View full text |Cite
|
Sign up to set email alerts
|

Circularly Polarized Luminescence and Circular Dichroisms in Small Organic Molecules: Correlation between Excitation and Emission Dissymmetry Factors

Abstract: by the recent rapid growth of interest in circularly polarized luminescence (CPL) of organic molecules, we have collected all the reliable CPL, as well as the corresponding circular dichroism (CD), data measured in fluid solutions. To analyze the correlation between CPL and CD, we employed the absorption and luminescence dissymmetry factors (g abs and g lum ) of the p-p* transition reported for chiral organic molecules of various categories, including planar chiral cyclophanes and helicenes, axially chiral bia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

40
497
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 571 publications
(556 citation statements)
references
References 201 publications
40
497
3
1
Order By: Relevance
“…Interesting is the comparison between the observed values of the dissymmetry factors with those of other helicenes and helicenoids . The g abs factors are well in the range of those observed for small [ n ]helicenes ( n =4–6).…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…Interesting is the comparison between the observed values of the dissymmetry factors with those of other helicenes and helicenoids . The g abs factors are well in the range of those observed for small [ n ]helicenes ( n =4–6).…”
Section: Resultsmentioning
confidence: 75%
“…As part of our own research program we have developed borylated arylisoquinoline (BAI) dyes, which in their N,C‐chelate variant are strongly emitting, solvatochromic, and two‐photon‐absorbing charge‐transfer fluorophores with application potential in bioimaging . With the idea to further enrich the photophysics of this fascinating platform we have built on their biaryl structure, which provides a means to arrive at dyes with helical chirality and the corresponding observation of interesting chiroptical properties, including the detection of circularly polarized luminescence (CPL) . The phenomenon is well established for supramolecular assemblies or nanostructures .…”
Section: Introductionmentioning
confidence: 99%
“…In that case, the differential absorption of the left‐ and right‐handed circularly polarized light in terms of molar absorptivities ( ϵ ) were considered, according to [ ϵ L ( λ )− ϵ R ( λ )]/[ ϵ L ( λ )+ ϵ R ( λ )]. As a result, efficient chiral emissions for both samples were set, since | g abs ( λ )|/| g lum ( λ )| ratios close to unity were obtained. Full stability against racemization of the two possible enantiomers, Plus (P ) and Minus (M) , was proved at the selected working conditions (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…And the correction of g lum =1.36×g abs +0.288 (r 2 =0.622) between CPL (g lum ) and CD (g abs ) was established, though fairly scattered,which demonstrated that the CPL dissymmetry factors were larger than, the CD dissymmetry factor, as shown in Figure . This relationship was different from that of small organic molecules, in which the general trend is g lum ≤g abs . The g lum /g abs ratio is above 1, which may promise metal ion complexes as CPL emitting materials a bright future.…”
Section: Resultsmentioning
confidence: 71%